Physico-Chemical Properties and Digestibility of Watermelon Vines Ensiled with Urea and Molasses - Atta Elmnan, Balgees A.; Mohamed , Awatif, B. A. (Journal of Veterinary Medicine and Animal Production, 2021)
An experiment was undertaken to estimate some physico-chemical properties and nutrients digestibility of watermelon vines ensiled with 2% urea and four different levels of molasses (0%, 5%, 10% and 15%) for 30 days. A completely randomized design with 4X5 (4 levels and 5 incubation period) for factorial arrangements was adopted for executing the experiment. The ensiled materials before and after 8, 15, 22, 30 days of incubation were tested for chemical composition, lactic and acetic acids concentration. In-vitro dry matter digestibility (IVDMD), in-vitro crude protein digestibility (IVCPD) and in-vitro crude fiber digestibility (IVCFD) were measured at the last day of the fermentation period. Addition of molasses and fermentation period had significant (P<0.05) effects on physico-chemical properties of the silage of watermelon vines. The pH value of the silage with 0% molasses was relatively higher than in silage with 15% of molasses and decreased with increasing fermentation period. The dry matter, crude protein contents, lactic and acetic acids concentration were significantly (P<0.05) increased with increasing molasses levels and fermentation times while crude fiber content was decreased. The highest values of IVDMD, IVCPD and IVCFD were recorded by silage supplemented with 15%, 10% and 5% of molasses, whereas the lowest value was recorded by 0% of molasses. The increase of molasses levels resulted in significant (P<0.05) improvement of physical characteristics (color and smell) of watermelon vines silage. This study indicated that the addition of molasses enhanced the physico-chemical and nutritional properties of the silage of watermelon vines incubated with urea.